2015
DOI: 10.1016/j.socscimed.2015.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Addressing domestic violence through antenatal care in Sri Lanka's plantation estates: Contributions of public health midwives

Abstract: Domestic violence in pregnancy is a significant health concern for women around the world. Globally, much has been written about how the health sector can respond effectively and comprehensively to domestic violence during pregnancy via antenatal services. The evidence from low-income settings is, however, limited. Sri Lanka is internationally acknowledged as a model amongst low-income countries for its maternal and child health statistics. Yet, very little research has considered the perspectives and experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 13 publications
1
46
2
2
Order By: Relevance
“…Limited consultation time, high workload and competing priorities, high staff turnover and lack of personal safety were other factors that obstructed the disclosure process (Infanti et al 2015;Iverson et al 2013;McCall-Hosenfeld et al 2014;Taft et al 2004;Salcedo-Barrientos et al 2011;Usta et al 2014;Visentin et al 2015;Taynan Sousa Porto et al 2014;Salgado Diez 2012). Moreover, some PCPs were reluctant to record VAW due to a lack of privacy and confidentiality at their primary care settings (Cox et al 2001;Peckover 2003): "I always write down a different cause for the IPV symptoms I treat, even in confirmed cases.…”
Section: A Need Of Structural-level Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…Limited consultation time, high workload and competing priorities, high staff turnover and lack of personal safety were other factors that obstructed the disclosure process (Infanti et al 2015;Iverson et al 2013;McCall-Hosenfeld et al 2014;Taft et al 2004;Salcedo-Barrientos et al 2011;Usta et al 2014;Visentin et al 2015;Taynan Sousa Porto et al 2014;Salgado Diez 2012). Moreover, some PCPs were reluctant to record VAW due to a lack of privacy and confidentiality at their primary care settings (Cox et al 2001;Peckover 2003): "I always write down a different cause for the IPV symptoms I treat, even in confirmed cases.…”
Section: A Need Of Structural-level Changesmentioning
confidence: 99%
“…Furthermore, sometimes the majority of PCPs felt helpless, frustrated, impotent, powerless and unable to help or respond to VAW; in consequence they lacked the confidence to deal with VAW (Cox et al 2001;De Oliveira and Godoy Serpa 2007;De Oliveira Gomes et al 2015;Kohler et al 2013;Papadakaki et al 2014;Infanti et al 2015;Signorelli et al 2013;Silva et al 2015;Vieira et al 2013;Visentin et al 2015;Webster et al 2006;Williston and Lafreniere 2013): "Sometimes myself I get depressed and frustrated, I don't know what to do… sometimes you ask yourself, did I do the right thing or not? Did I help or did I make it worse?"…”
Section: Struggling With the Emotional Impact That Vaw Evokedmentioning
confidence: 99%
See 2 more Smart Citations
“…In a routine ANC setting this would or should be done by health care providers. A qualitative study of public health midwives in Sri Lanka revealed that midwives acknowledged their unique status as trusted health providers in the communities and apply creative strategies (threaten abusive husbands, show images of babies born with deformities) to address DV among pregnant women [38].…”
Section: Discussionmentioning
confidence: 99%